Two-Year Outcomes of Asymptomatic vs. Symptomatic Patients After Deferral of Revascularization Based on Fractional Flow Reserve ― Insights From the J-CONFIRM Registry ― - Horie, Kazunori (Circ Rep, 2020)
Background: The effect of symptoms on clinical outcomes after deferral of revascularization based on fractional flow reserve (FFR) remains poorly understood. Methods and Results: From the J-CONFIRM (Long-Term Outcomes of Japanese Patients With Deferral of Coronary Intervention Based on Fractional Flow Reserve in Multicenter) Registry, this study evaluated 1,215 patients with stable coronary artery disease, including symptomatic and asymptomatic patients (n=571 and 644, respectively). The primary endpoint was the cumulative 2-year incidence of target vessel failure (TVF), including cardiac death, target vessel-related myocardial infarction (TVMI), and clinically driven target vessel revascularization (CDTVR). An inverse probability weighted analysis was performed to adjust for the differences in baseline clinical characteristics between the 2 groups. At 2 years, the TVF rate did not differ significantly between symptomatic and asymptomatic patients (6.5% vs. 4.9%, respectively; P=0.15) or between symptomatic and asymptomatic patients with lesions with an FFR ≤0.80 (8.0% vs. 12.3%, respectively; P=0.20). Conversely, symptomatic patients showed significantly higher rates of TVF (6.2% vs. 3.3%; P=0.01) and CDTVR (6.2% vs. 3.1%; P=0.009) than asymptomatic patients, regardless of negative FFR values (>0.80). Conclusions: Despite negative FFR values, symptomatic patients were at higher risk of TVF than asymptomatic patients, driven primarily by a higher rate of CDTVR. Conversely, those with a positive FFR were likely to develop TVF regardless of their symptoms.